EFFICIENCY OF OPERATION OF THE FIRE SAFETY SUBSYSTEM OF THE HYDROGEN STORAGE AND SUPPLY SYSTEM - Abramov, Yu.; Kryvtsova, V.; Mykhailiuk, A. (Municipal economy of cities. Series: «Economy science», 2024)
Hydrogen may become one of the most valuable energy carriers in the 21st century. A big step to this is the safe, compact, and cost-effective storage of hydrogen provided by hydrogen storage systems (HSS). One of the operating system elements of the hydrogen storage and supply system is its fire safety subsystem. The effectiveness of such a subsystem’s functioning depends on a conditional probability that this subsystem correctly recognises the actual state of the hydrogen storage and supply system. We carry out the formalisation of the operation of the fire safety subsystem of the hydrogen storage and supply system in the form of a graph of its states. The study considers three modes of operation of such a subsystem: control, testing, and self-control. We build a weight matrix of the fire safety subsystem states. Its elements include the intensity of transitions from one state to another, the recovery intensity, and the completeness of control and testing. The study shows that the roots of the system of Kolmogorov equations determine the efficiency of the functioning of the fire safety subsystem of the hydrogen storage and supply system. We represent this system of equations in matrix form, with the main matrix having a size of 8×7. Next, we obtain expressions for the roots of such a system of comparisons and construct an expression for the efficiency of the fire safety subsystem’s functioning of the hydrogen storage and supply system. This expression applies to all three modes of operation of such a fire safety subsystem. The considered typical modes of operation of the fire safety subsystem of the hydrogen storage and supply system are control mode, control mode with self-control, and control and testing mode. For each of these modes, we obtain expressions that describe their effectiveness. It is necessary to note that the magnitudes of recovery intensities, in contrast to transition intensities, can vary. We further provide an example of choosing the intensities of restoration of the subsystem during its control using the acceptance criterion for the probability of finding the subsystem in a state corresponding to the fire-hazardous state of the hydrogen storage and supply system.